DIAGNOSTIC ACCURACY OF ECG TO DETECT LEFT VENTRICULAR HYPERTROPHY IN HYPERTENSIVE PATIENTS - SHAKEEL, AA; SHOUKAT, M; ULLAH, N; QURESHI, AE; RAHI , MN; SHAFI , T (Biological and Clinical Sciences Research Journal, 2023)
Hypertension is a significant public health problem with an increasing prevalence worldwide. Hypertension is a robust risk factor for Left Ventricular Hypertrophy (LVH). LVH is a compensatory adaptive response of myocardium against increased afterload to reduce wail stress and maintain pump function and is commonly seen in hypertensive patients. LVH is independently associated with an enhanced risk for myocardial infarction. The study's objective was to determine the diagnostic accuracy of electrocardiography to determine LVH in patients with hypertension by taking Echo as the gold standard. This cross-sectional study was conducted at the Cardiology Department, Rehmatul-Lil-Alameen Institute of Cardiology, Lahore, from July 25, 2019, to December 26, 2019. 236 hypertensive patients fulfilling the inclusion criteria were enrolled in the cardiology department. All patients were then undergoing ECG and Echo. Echo was performed by cardiologists who were also blind to the study group to which these ECHO belong. Outcome variables include the number of hypertensive patients having LVH on Echo and ECG. The mean age of patients was 58.24±14.29 years. There were 159(67.4%) males and 77(32.6%) females. The mean BMI of the patients was 25.12±1.94. The mean duration of hypertension was 15.14±6.76years. Sensitivity and specificity of ECG were 79.19% and 80.95%, respectively, and PPV & NPV was 91.95% and 58.62%, respectively; overall diagnostic accuracy was 79.66%. Based on the results, it can be concluded that the ECG has a high specificity, PPV, and diagnostic accuracy for the diagnosis of left ventricular hypertrophy in patients with hypertension by taking Echo as the gold standard.